2022
DOI: 10.1097/ccm.0000000000005767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Admission and Discharge Times on Hospital Mortality in Patients With Sepsis

Abstract: To assess whether the time of admission/discharge time from the ICU and weekend admission are independently associated with hospital mortality in critically ill patients with sepsis.DESIGN: Retrospective study. Each 24-hour period (08:00 to 07:59 hr) was split into three time periods, defined as "day" (08:00 to 16:59 hr), "evening" (17:00 to 23:59 hr), and "night" (00:00 to 07:59 hr). Weekends were defined as 17:00 hours on Friday to 07:59 hours on Monday. Multivariate logistic regression models were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The 22 studies which were selected for full-text analysis underwent detailed examination and nine were found to be appropriate based on the inclusion criteria. [14][15][16][19][20][21][22][23][24] The remaining 13 studies were excluded for reasons mentioned in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 22 studies which were selected for full-text analysis underwent detailed examination and nine were found to be appropriate based on the inclusion criteria. [14][15][16][19][20][21][22][23][24] The remaining 13 studies were excluded for reasons mentioned in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study from Brazil has shown that a reduced nurse-to-patient ratio, absence of checklists, and fewer standardized protocols during weekends may partly explain a higher risk of ICU mortality on weekends. 32 Zhou et al 15 have also shown that while no weekend effect was not on mortality rates of sepsis patients, the patient-to-nurse ratio was an independent predictor of outcomes. Secondly, it has been postulated that patients reporting on weekends are often sicker.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study conducted in the UK no influence of week and time of admission on mortality could be found. 8 Similarly, ICU admission time and weekend admission were not independent risk factors of hospital mortality in critically ill patients with sepsis in a study done by Zhou et al 19 …”
Section: Discussionmentioning
confidence: 90%
“…In China, some studies have explored the weekend effect on acute myocardial infarction ( 18 ), subarachnoid hemorrhage ( 19 ), and sepsis patients ( 20 ). A longer hospital length of stay was observed among stroke patients with weekend admissions in a Taiwanese study ( 21 ).…”
Section: Introductionmentioning
confidence: 99%